(untitled) - Benson, Lee (Philadelphia, Pennsylvania, 1972)
This is a stunning paper on what is to be done with and about the Middle Period. The analysis is impressive, and the writing extraordinarily clear and vigorous and ordered.
Keywords: History; Study and teaching